Early outcome in endovascular management of iliac artery - كفا, علي (Latakia University Journal -Medical Sciences Series, 2022)
Background: Peripheral arterial disease (PAD) considered one of the most important health problems due to functional disability, high morbidity and mortality associated with critical ischemia. There is a n important evidence support the safety and effectiveness of endovascular treatment in patients with iliac occlusive disease. Objective: the study aimed to evaluate the early outcome of endovascular management (stenting) in patients with iliac occlusive disease. In addition to, determining the rate of primary patency and complications resulting of the procedure. Patients and methods: a prospective observational analytic study conducted for one-year period (1/1/2020 – 31/12/2020) at Tichreen University Hospital in Lattakia – treatment (stenting). Result: mean age was 57.5±5.8 (56.3% males, 34.7% females). Ankle-Brachial Index (ABI) ranged from 0.73 to 0.95 pre-procedure with mean value 0.66±0.03. According to Rutherford classification, 66.3% of patients were group 3. The lesion located in common iliac artery in 62.7% of the patients, external iliac artery in 37.3%. There was a significant increasing in ABI value after stenting (42.4%). One-year patency was 94.7%, while 4 patients (5.3%) represent occlusion. There were no local complications or mortality. Conclusion: Management of iliac occlusive lesions by endovascular stenting considered as an effective safe method.